Assessment as Learning (AaL)-oriented IPAS student worksheet to enhance the critical thinking skills of fourth-grade elementary school students - Dhea Ovita; Pramudiyanti; Ryzal Perdana; Fatkhur Rohman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The research objective is to develop a science and social science student worksheet (LKPD IPAS) oriented toward Assessment as Learning (AaL) to enhance the critical thinking skills of fourth-grade elementary school students. This study employs a Research and Development (R&D) approach using the ADDIE development model. The research population comprises fourth-grade students from the Ki Hajar Dewantara Cluster in Tanjung Harapan in Central Lampung. The research sample includes fourth-grade students from SDN 1 Tanjung Harapan. Data collection was carried out using valid and reliable test instruments. The results indicate that: (1) the AaL-oriented LKPD IPAS is valid, as demonstrated by the validation results from content experts (0.6240), media experts (0.7639), and language experts (0.6250); (2) the LKPD IPAS is practical for use, as indicated by the practicality percentages from teachers (96%) and students (91.9%); and (3) the LKPD IPAS is effective in improving students’ critical thinking skills, as evidenced by an N-Gain score of 0.6351. Therefore, it can be concluded that the AaL-oriented LKPD IPAS is valid, practical, and effective in enhancing the critical thinking abilities of fourth-grade elementary school students.